Using "theory of change" to improve agricultural research: recent experience from Tanzania. Issue 7 (3rd October 2019) - Omore, Amos; Kidoido, Michael; Twine, Edgar; Kurwijila, Lusato; O'Flynn, Maureen; Githinji, Julius
ABSTRACT: Demonstrating how agricultural research contributes to development outcomes is difficult but necessary given competing demands for scarce resources. This article summarises an adaptation of the "theory of change" approach and lessons derived from its application to improve the design and implementation of an agricultural research for development programme for greater impact. It was applied to Maziwa Zaidi, a programme that tested integrated interventions to catalyse the transformation of smallholder dairy value chains in Tanzania. Despite challenges, the approach was found useful for planning, communication, managing complexity, monitoring behavioural changes and deriving lessons to adapt future programme activities amid complexity and uncertainties.